#TITLE_ALTERNATIVE# - FADLI SHIDDIQY , AKIF
In the recent years, Worldwide Interoperability for Microwave Access (WiMax) technology has been one hottest commodity in telecommunication industry. The main reason behind this phenomenon is the ability of WiMax technology to provide people with higher speed data access. As the flow of material and information growing significantly in the globalization era, there is an excessive demand towards technologies that can solve the issue. WiMax, as one of the newest evolution in telecommunication technology, becomes one of few technologies that can provide the right answers. From data capacity perspective, WiMax technology can provide data transfer two times as fast as the most current Global System for Mobile communications (GSM) technology, which is; High-Speed Downlink Packet Access (HSDPA). Moreover, unlike the other similar kinds of technology, every WiMax-based component nowadays must be standardized into IEEE 802.16 standard which means lower cost regarding to lower economic of scale. Because those advantages, currently there are many enterprises interested to use WiMax technology in order to operate their business in telecommunication industry. NetMax, as one of companies running in internet and multimedia services, strive to exploit WiMax technological advantages into competitive advantages in the market. By using WiMax as technological base, NetMax is able to provide faster internet access towards its customers within reasonable price. Moreover, from operational point of view, NetMax starts to expand its market from region Jakarta-Bogor-Depok-Tangerang-Bekasi (Jabodetabek) due to several reasons which are; availability of adequate supporting infrastructures and high internet demand. From this region, NetMax then will start to expand the market towards other region in Indonesia, especially after Indonesia Government provide WiMax regulation which expected to happen in the year 2013. Furthermore, from financial point of view, NetMac project is expected to generate Net Present Value (NPV) and Internal Rate of Return (IRR) equivalent to IDR 282,662,558,040 and 23%. Meanwhile, NetMax will reach Break Even Point (BEP) in 3 years 1 month and 7 days after initial investment.